HEPATITIS C SEROPOSITIVITY AMONG CHRONIC LIVER DISEASE PATIENTS IN HAZARA, PAKISTAN - Khan, Taher Salim; Rizvi, Farhat; Rashid, Abdur (Journal of Ayub Medical College Abbottabad, 2003)
Background: Hepatitis C is rapidly emerging as a major health problem in developing countries including Pakistan. The present study was conducted to document the frequency of Hepatitis C seropositive individuals reporting for hepatitis testing at a referral laboratory. Methods: Serum samples were collected from 614 people (436 males and 178 females) referred for chronic liver disease from all parts of Hazara division during the period July 2000 to July 2002. Hepatitis tests were performed by DOT immuno-chromatographic method for anti HCV antibodies. Results: A total of 251 (40.8%) sera tested positive for anti HCV antibodies, including 184 males (73.3%) and 67 females (26.7%). Of 436 males, 184 (42.2%) tested positive, while among females, 67/178 (37.6%) tested positive; this difference is not statistically significant. However the male/female ratio referred for testing was 2.4:1. Conclusion: There is a high frequency of HCV seropositive individuals of both sexes among patients referred for chronic liver disease. The frequencies obtained for Hazara division compare well with figures from other parts of Pakistan as well as developing countries. The male/female ratio could simply be a reflection of more males coming for treatment and testing in our setting. Key Words: Hepatitis C, Hepatitis C Antibodies, Hepatitis C Antigen.